Fluorenyl Based Macrocyclic Polyradicaloids - Lu, Xuefeng; Lee, Sangsu; Hong, Yongseok; Phan, Hoa; Gopalakrishna, Tullimilli Y; Herng, Tun Seng; Tanaka, Takayuki; Sandoval-Salinas, María Eugenia; Zeng, Wangdong; Ding, Jun; Casanova, David; Osuka, Atsuhiro; et al. (Journal of the American Chemical Society, 2017)
Synthesis of stable open-shell polyradicaloids including control of intramolecular spin–spin interactions is a challenging topic in organic chemistry and materials science. Herein, we report the synthesis and physical characterization of two series of fluorenyl based macrocyclic polyradicaloids. In one series (FR-MCn, n = 4–6), the fluorenyl radicals are directly linked at 3,6-positions; whereas in the other series (MC-FnAn, n = 3–5), an additional ethynylene moiety is inserted between the neighboring fluorenyl units. To access stable macrocyclic polyradicaloids, three synthetic methods were developed. All of these stable macrocycles can be purified by normal silica gel column chromatography under ambient conditions. In all cases, moderate polyradical characters were calculated by restricted active space spin-flip method due to the moderate intramolecular antiferromagnetic spin–spin interactions. The excitation energies from the low-spin ground state to the lowest high-spin excited state were evaluated by superconducting quantum interference device measurements. Their physical properties were also compared with the respective linear fluorenyl radical oligomers (FR-n, n = 3–6). It is found that the geometry, i.e., the distortional angle and spacer (w or w/o ethynylene) between the neighboring fluorenyl units, has significant effect on their polyradical character, excitation energy, one-photon absorption, two-photon absorption and electrochemical properties. In addition, the macrocyclic tetramers FR-MC4 and MC-F4A4 showed global antiaromatic character due to cyclic π-conjugation with 36 and 44 π-electrons, respectively.